Ausgewählte Abendmahlsschriften: Mit einer historischen Einführung von Sven Grosse (Evangelische Verlagsanstalt, 2023)
John Oekolampad (1482–1531) is known as the reformer of Basel. His writings have – except some few and marginal cases – not been edited since the prints of the 16th century. With this publication the first modern edition of essential writings of Oekolampad has come to existence: his most important writings on the right understandig of the eucharist. Oekolampad has, publishing them, been on of the initiators of the first controversy on the eucharist among the reformers. Rejecting the real presence of Christ’s body and blood he took a position together with Zwingli against Johannes Brenz and Martin Luther. This edition comprehends two Latin and three German writings, by which this controversy can be retraced.